IMPLEMENTASI KERJASAMA SISTER CITY KOTA BANDUNG - KOTA FORT WORTH DI BIDANG PENDIDIKAN - Intan Rodiah Gusman (UIR Press, 2020)
In the current era of globalization, all countries are required to build cooperation with other countries, the reason is that through the cooperation of one country with another country, they can connect with each other in order to realize a common goal in accordance with the interests of their respective countries. Therefore, cooperation is expected to create world peace, so that the dark tragedy that occurred during World War I and World War II does not repeat again. However, we need to know that the cooperation that is built is not only carried out by the central government, because the central government will not be able to handle overall cooperation in a country, therefore the government makes a policy to allow local governments to handle international cooperation with other countries with a system